229k views
4 votes
How do you solve this problem: 2y(6 - 1)(6 - 1) = - 200

2 Answers

4 votes

Solve: 2y(6 - 1)(6 - 1) = - 200


Simplify both sides of the equation:


50y = - 200



Divide both sides by 50


50y/50 = -200/50


y = - 4





Answer: y = - 4





Hope that helps!!!!!!! (Answer: y = - 4)

User Zensaburou
by
5.6k points
3 votes

Hey there! :)


2y(6 - 1)(6 - 1) = -200


Simplify from the parenthesis.


2y(5)(5) = -200


Simplify.


2y(25) = -200


Simplify.


50y = -200


Divide both sides by 50.


50y ÷ 50 = -200 ÷ 50


Simplify.


y = -4


~Hope I helped!~

User Rahul Ahire
by
7.2k points